Detergent protease exposure and respiratory disease: case–referent analysis of a retrospective cohort. Issue 11 (29th June 2009) - Brant, A; Upchurch, S; van Tongeren, M; Zekveld, C; Helm, J; Barnes, F; Newman Taylor, A J; Cullinan, P
Abstract : Objectives: To examine the relationship between protease exposure and respiratory disease in a cohort of detergent enzyme manufacturers. Methods: Case–referent analysis of a cohort of employees working in a European detergent factory between 1989 and 2002. Cases with new lower or upper respiratory disease were ascertained by examination of occupational health records and matched to referents on date of first employment. Personal exposures to airborne detergent protease were estimated, using a job exposure matrix, from >12 000 measurements taken in the factory during the period of study. Results: We found clear, monotonic relationships between estimated protease exposure and both lower and upper respiratory disease. After control for age, sex and smoking, the odds ratio of lower respiratory disease was significantly elevated (1.98, 95% CI 1.04 to 3.79) in those employees working in jobs in the highest quartile of protease exposure (geometric mean 7.9 ng.m −3 ). For employees with upper respiratory disease, the risk was significantly elevated at a lower level of estimated protease exposure (geometric mean 2.3 ng.m −3 ). Conclusions: These findings provide strong evidence of an association between detergent enzyme exposure and the development of respiratory disease in an occupational setting. Using the routinely collected information on specific sensitisation and the close attention to workplace exposures that are characteristic of this industry, it should be possible to derive meaningful occupational exposure standards for most detergent enzymes.